2018
DOI: 10.1016/j.jconrel.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Radiopharmaceutical enhancement by drug delivery systems: A review

Abstract: Great advancements have been made with the development of novel systems incorporating nuclear entities in drug delivery systems, with the possibility of reshaping the nuclear medicine landscape. Nonetheless, translation from preclinical evaluations to clinical use is lacking and serious investment needs to be made towards this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 206 publications
(211 reference statements)
0
35
0
1
Order By: Relevance
“…To overcome these above limitations, the booming nanoscale drug delivery systems (NDDS) have offered innovative ideas and approaches to fight malignant tumours, exhibiting high antitumour activity and reduced side effects in humans through controlled tumour-oriented drug release [5,6]. Numerous researches indicated that NDDS can reduce drug toxicity, prevent early drug release, protect drugs from rapid blood/renal clearance and achieve the preferential accumulation of drugs within solid tumours with enhanced permeability and retention (EPR) effect [7][8][9][10]. In addition, precise tumour imaging has been recognized to be an important strategy for image-guided cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these above limitations, the booming nanoscale drug delivery systems (NDDS) have offered innovative ideas and approaches to fight malignant tumours, exhibiting high antitumour activity and reduced side effects in humans through controlled tumour-oriented drug release [5,6]. Numerous researches indicated that NDDS can reduce drug toxicity, prevent early drug release, protect drugs from rapid blood/renal clearance and achieve the preferential accumulation of drugs within solid tumours with enhanced permeability and retention (EPR) effect [7][8][9][10]. In addition, precise tumour imaging has been recognized to be an important strategy for image-guided cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic nanoparticles of lanthanum phosphate containing 225 Ac and monoclonal antibodies for targeting have been optimized to exhibit less isotope leakage and tested for efficacy in vivo. Drug delivery systems for 233 Ra are also under development with different nanoparticle systems like lanthanum phosphate, nanozeolite, hydroxyapatite, and iron oxide nanoparticles 123 . A quantum dot–antibody system comprising Cd 125m Te/ZnS ( t 1/2 , 57.4 days) QD have been shown to accumulate in the lung compared with the spleen and the liver, which has been direct consequence of competitive interaction between vascular and reticuloendothelial systems 124,125 …”
Section: Different Nanoparticle Systems Used For Delivery Of Radiophamentioning
confidence: 99%
“…When a nanosystem acts at the same time as an imaging and therapeutic agent, it is known as a theranostic [53]. The imaging function can be achieved assembling nanosystems attached to radionuclides such as the technetium-99-metastable and other imaging agents which can give real-time information about the function of the nanosystem in the body [54,55].…”
Section: Nanosystemsmentioning
confidence: 99%